Analysis of pre-certification of palm oil protection implementation for forest protection at PTPN XIV Persero unit malili. Issue 1 (October 2021) - Iriani, I; Sahide, M A K; Sabar, A
Abstract: This research was conducted to analyze the extent to which the input of palm oil certification policy at PT Perkebunan Nusantara (PTPN) XIV Persero Unit Malili on aspects of forest protection, and to see the certification system applied by PTPN XIV Persero Unit Malili whether it uses ISPO standards and RSPO standards. In this study, several data sources were used relating to the principles, criteria, and indicators of the ISPO and RSPO certification standards. Data were collected using interviews, observation, and literature study from some related literature. From this research, it is known that PTPN XIV Unit Malili has not been verified by ISPO or RSPO but in its implementation, it is currently preparing to be certified ISPO. Forest protection from the aspect of biodiversity protection is fulfilled, however, several plantation areas have become disputes with the community and there are claims of forest areas managed by PTPN XIV where the area has not been released. Form of forestry supervision, namely KPH Larona Malili, in the claim of this area by conducting patrols and visits to plantation sites and cooperation. Transparency from the company, the community, and related institutions can be a driving force for the realization of appropriate and sustainable plantation practices.